Peran Investasi Asing Texas Pacific Group (TPG) di Bank BTPN Terhadap Pemberdayaan Perempuan Indonesia: Studi Kasus Kredit Mikro BTPN 2008 - 2012 - Arie Susanto (Solidaritas: Jurnal Ilmu-Ilmu Sosial, 2022)
Various efforts have been made by the Indonesian government to reduce gender inequality between men and women. For this reason, structured and sustainable efforts are needed for the creation of women's empowerment in Indonesia, especially the fact that Indonesia has ratified the CEDAW Convention. Efforts to create empowered women are processes carried out by all elements in a country. The existence of foreign investment by the Texas Pacific Group (TPG) in Bank BTPN opens opportunities for women in general and women micro-entrepreneurs to become empowered through loans. The existence of TPG in BTPN between 2008 – 2012 changed the direction of the business from serving retired customers to the micro credit market where the micro business sector was dominated by women. This study uses a descriptive-qualitative method with primary data sources in the form of annual reports from BTPN and TPG and data, reports, and publications published by TPG and BTPN. The researchers also used secondary data sources to analyze and perform data reduction and verification. For this reason, the researcher uses a study of feminism theory and modernization theory which is in accordance with the theme of women's empowerment being studied. The results of this study include; (1) the presence of TPG foreign investment in BTPN for the period 2008 - 2012 brought new business policies that had a direct impact on women in Indonesia through the provision of women-friendly loans; (2) Improving the quality of human resources for women's micro-enterprises through a series of trainings has a vital role in empowering Indonesian women themselves.